Remittances and domestic investment in BRICS: Does financial development matter? - Tsaurai, Kunofiwa (Asian Economic and Financial Review, 2025)
The study investigated the impact of remittances on domestic investment within the BRICS region. It also explored the complementarity effect (remittance and financial development) on domestic investment using the same data set. The existing literature shows a lack of consensus; hence, their findings are mixed, inconsistent, and divergent, and they show an absence of consensus. The study employed fixed effects, fully modified ordinary least squares (FMOS), and pooled ordinary squares (OS). Panel data used ranged from 1989 to 2020. Using personal remittance inflow per capita as a proxy, remittance’s influence on domestic investment was positive and significant across all three panel methods. When personal remittances received were employed as a proxy, remittance’s impact on domestic investment was significantly deleterious under the pooled OS. Financial development significantly improved domestic investment, as observed by Pooled OS (all three models) and FMOS (model 3). Pooled OS (model 1) and FMOS (model 2) produced results that show that financial development improved remittances’ ability to significantly improve domestic investment. The study shows that remittances are a critical element in enhancing domestic investment in BRICS. BRICS nations are urged to develop policies that enhance financial development and remittance inflow to improve domestic investment.